CaMKII Signaling Stimulates Mef2c Activity In Vitro but Only Minimally Affects Murine Long Bone Development in vivo - Amara, Chandra S.; Fabritius, Christine; Houben, Astrid; Wolff, Lena I.; Hartmann, Christine (Frontiers in Cell and Developmental Biology, 2017)
The long bones of vertebrate limbs form by endochondral ossification, whereby mesenchymal cells differentiate into chondrogenic progenitors, which then differentiate into chondrocytes. Chondrocytes undergo further differentiation from proliferating to prehypertrophic, and finally to hypertrophic chondrocytes. Several signaling pathways and transcription factors regulate this process. Previously, we and others have shown in chicken that overexpression of an activated form of Calcium/calmodulin-dependent kinase II (CaMKII) results in ectopic chondrocyte maturation. Here, we show that this is not the case in the mouse. Although, in vitro Mef2c activity was upregulated by about 55 fold in response to expression of a dominant-active form of CaMKII (DaCaMKII), transgenic mice that expressed the DaCaMKII under the control of the Col2a1 regulatory elements display only a very transient and mild phenotype. Here, only the onset of chondrocyte hypertrophy at E12.5 is accelerated. It is also this early step in chondrocyte differentiation that is temporarily delayed around E13.5 in transgenic mice expressing the peptide inhibitor CaM-KIIN from rat (rKIIN) under the control of the Col2a1 regulatory elements. Yet, ultimately DaCaMKII, as well as rKIIN transgenic mice are born with completely normal skeletal elements with regard to their length and growth plate organization. Hence, our in vivo analysis suggests that CaMKII signaling plays a minor role in chondrocyte maturation in mice.